Relationship between total thyroxine, thyroid palpation and a clinical index in hyperthyroid and healthy cats and cats with other diseases. Issue 8 (August 2019) - Wehner, Astrid; Koehler, Ines; Ramspott, Sabine; Hartmann, Katrin
Objectives: Present-day diagnosis of hyperthyroidism is often established in the early stages where clinical signs and physical examination findings typically associated with the disease may not yet be present. The purpose of this study was to investigate thyroid palpation score (TPS), total thyroxine (T4), body weight, body condition score and a clinical scoring index, which assesses severity of illness and quality of life, in untreated hyperthyroid cats, healthy cats and cats with non-thyroidal illness. Methods: Fifty-five cats with hyperthyroidism, 45 healthy cats and 327 euthyroid cats with non-thyroidal disease were prospectively enrolled. A Kruskal–Wallis test was used to determine any differences between metric data. A χ 2 test was applied to compare nominal data between the three subgroups. Correlation between two variables was analysed using Spearman's correlation coefficient. Results: Almost 80% of the hyperthyroid cats and up to 20% of the healthy cats and cats with non-thyroidal illness had a palpable thyroid gland. Median TPS in hyperthyroid cats was 2, which was significantly higher compared with the other groups. Although there was a significant correlation between TPS and T4 when evaluating all cats, this could not be demonstrated in the three subgroups. Hyperthyroid cats with larger thyroid glands (TPS >3) did not have higher T4 levels. Hyperthyroid cats with lower clinical scores had significantly higher T4 levels compared with hyperthyroid cats with higher scores. Hyperthyroid cats were older and had lower body weights and body condition scores than other cats. Conclusions and relevance: Hyperthyroid cats were commonly found to have palpable thyroid glands, but they were smaller than previously reported.